CPC351/CPM351 – Principles of Data Analytics (Prinsip Analitik Data) - February/March 2022 - PPSKOM, Pusat Pengajian Sains Komputer (2022)
First Semester Examination 2021/2022 Academic Session February/March 2022 CPC351/CPM351 – Principles of Data Analytics (Prinsip Analitik Data)